Diferentes níveis de grão de milheto (Pennisetum glaucum (L.) R. Brown) na alimentação de suínos - Bastos, Alexandre Orio; Landell Filho, Luiz De Carvalho [UNESP]; Passipieri, Milton [UNESP]; Pereira Bastos, João Francisco [UNESP] (My University, 2002)
A trial was carried out to determine the viability of pearl millet inclusion (Pennisetum glaucum (L.)R. Brown) on pigs feeding, in the growing and finishing phases, considering their effects on daily feed intake, average daily gain and feed conversion. The effect of increasing dietary pearl millet levels on the carcass characteristics was also observed. Sixty barrows, commercial hybrids, averaging 22.7kg were used. A completely randomized experimental design, with five treatments (0, 15, 30, 45 and 60% pearl millet in the diets), six replicates and two animals per unit experimental, was used. The values were fitted to polynomial regression. In the growing, finishing phase and in total period, average daily gain and feed conversion were not affected of using pearl millet on feeding. No effect of increasing dietary pearl millet levels on performance in the growing and finishing phases, nor on the carcass characteristics, was observed. It was concluded that peal millet addition in the pig diets is viable. Considering the ingredient prices during this trial, the addition of 45% pearl millet was the most economically efficient.
Different levels of pearl millet (Pennisetum glaucum (L.) R. Brown) in the pigs feeding
Keywords: Alternative feed; Carcass characteristics; Economic viability; Performance